Einstein : his life and works - Gamalath, K.A.I.L. Wijewardena (New Delhi, Narosa, 2012)
EINSTEIN: His Life and Works introduces the genius Albert Einstein, gives a detailed biography and expounds his most important scientific theories in an attractive pictorial form. Almost all his scientific works are discussed briefly, based on published articles. The major works, the Annus Mirabilis papers on light quantum hypothesis, molecular dimensions and Brownian motion, mass energy equivalence and special theory of relativity including Minkowskian four dimensional spacetime are discussed in detail. His greatest cosmological theory, the general theory of relativity is presented by introducing equivalence principle and field equation. The gravitational effect on time, length and light are explained using the Schwarzschild solution. His other major contributions to physics as well as his many attempts on unified field theory are also presented.
Notes 355-376p.; Index 377-386p.
Keywords: Einstein - biography; Einstein - life and work; Physics